Development and characterization of soy protein films incorporated with cellulose fibers using a hot surface casting technique. Issue 1 (January 2015) - Jensen, A.; Lim, L.-T.; Barbut, S.; Marcone, M.
Abstract In this study, cellulose-soy protein isolate (SPI) composite films were prepared using a hot surface casting technique. The cellulose microfibrils for the films were extracted from soybean pods and stems using a combined acid-alkaline hydrolysis and high-pressure homogenization treatment. For comparison, TiO2-SPI composite films were also prepared using TiO2 nanoparticles as filler. Mechanical and barrier properties (water vapor, and oxygen permeability) of these files were evaluated under different relative humidity (RH) conditions. In general, tensile strength (TS) and Young's modulus (YM) decreased and elongation at break (EAB) increased with increasing RH. Among the composites tested, the 5 g:95 g fiber:SPI film exhibited significant (p-value < 0.05) improvements in TS and YM but decreased EAB as compared to the neat SPI. By contrast, TiO2 composites possessed similar TS, YM, and EAB values as the control film. Barrier properties were comparable across all samples, and decreased with increasing RH. Samples were characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, and atomic force microscopy.